Multi-advantageous sorghum as feedstock for biogas production: A comparison between single-stage and two-stage anaerobic digestion systems. (15th July 2022) - Pasteris, Andrea Marina; Heiermann, Monika; Theuerl, Susanne; Plogsties, Vincent; Jost, Carsten; Prochnow, Annette; Herrmann, Christiane
Abstract: Anaerobic digestion (AD) is a keystone in the circular economy concept. The produced biogas can be demand-driven controlled and regionally adaptable, but sustainable feedstocks are required. Sorghum is a valuable alternative considering its bioenergy potential and wide adaptability to different environmental conditions. In this study, AD of sorghum silage was performed in a single-stage continuously stirred tank reactor (CSTR) and in a two-stage leach-bed reactor (LBR) system. The two-stage LBR system revealed higher methane yields (434 LN kgVS −1 ) compared to the single-stage CSTR (308 LN kgVS −1 ). Methane content of biogas ranged from 53 to 59% in both systems. Only the CSTR exhibited acids accumulation, led by propionic acid concentration (2.0 g L −1 ). Buffer capacity of the two-stage LBR system was superior to the CSTR. Technical disruptions and constant ammonium content declination were shown in both systems, associated to inherent characteristics of fibrous sorghum. AD of sorghum biomass, however, can be effectively performed under controlled conditions, generating high methane yields in both types of systems. Highlights: Mesophilic AD of fibrous sorghum in a single- and in a two-stage digestion system. Accumulation of volatile fatty acids occurred during experiments in CSTR. Two-stage system produced higher methane yields and showed better process stability. A constant declination of the ammonium-nitrogen content was observed. Fibrous sorghum caused technical disruption in both types of system.